The Crisis Management Of Province Committee Board(DPW) Prosperous Justice Party (PKS) East Java (Descriptive Qualitative Study of Crisis Management of Public Relations DPW PKS East Java to Defensed Electability Party On General Election 2014) - Auza'I, Burhanuddin; , M. Toharuddin, MA; , Nieldya Nofandrilla, MA (2014)
PKS DPW East Java isthepoliticalaspirationsof citizenswho agree with the party platform. Bribery case involving President of PKS makes public relations(PR) as the frontliner in dealing withthe crisismanagement. The purposeof this studyis determine crisis management of publicrelations DPW PKS East Java to defensed electability party on general election 2014,the research methodused is descriptive qualitative explaining PR crisis management actions. Datawas collected using in-depth interview sandn on participant observation using three informants by purposive sampling. PR training program is empowerment, creating the oresolid internal communication. Political communication in theregion of Matraman is accomplised using national symbols so PKS is nationalis,whilein thetapalkudaarea PKS is described not as the Islam extrimist so PKS same with majority santri. AYTKTM program(no matter what happens we are still serving) and active in twitter managed to improve the image of PKS in East Java.